2017
DOI: 10.1002/2017jd026788
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Biomass Burning Emissions on Major Inorganic Aerosols and Their Precursors in the U.S.

Abstract: The primary sources for inorganic aerosols from biomass burning are rather negligible, but they are predominantly formed chemically following emission of their precursors (e.g., SO2, NH3, HOx, and NOx). The biomass burning contributions to some of the precursors can be considerable. Accordingly, we quantify the impact of the emissions on major inorganic aerosols in April–October 2012–2014 using a regional model simulation verified by extensive surface observations throughout the U.S. Simulated CO enhancements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…Souri et al (2017) showed that biomass burning emitted negligible particulate nitrate but considerable amounts of gaseous precursors (NO x ). Souri et al (2017) showed that biomass burning emitted negligible particulate nitrate but considerable amounts of gaseous precursors (NO x ).…”
Section: Surface Smoke Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Souri et al (2017) showed that biomass burning emitted negligible particulate nitrate but considerable amounts of gaseous precursors (NO x ). Souri et al (2017) showed that biomass burning emitted negligible particulate nitrate but considerable amounts of gaseous precursors (NO x ).…”
Section: Surface Smoke Chemical Compositionmentioning
confidence: 99%
“…We also find that nitrate and sulfate concentrations are increased on smoky days. Souri et al (2017) showed that biomass burning emitted negligible particulate nitrate but considerable amounts of gaseous precursors (NO x ). Their work demonstrated that the formation of aerosol-phase nitrate particles was mainly from the conversion of NO x .…”
Section: Surface Smoke Chemical Compositionmentioning
confidence: 99%
“…As for NH 3 , over 90 % of the NH 3 emissions in terrestrial ecosystems originate from agricultural production, such as livestock breeding and NH 3 -based fertilizer application (Paulot and Jacobs, 2014; Kang et al, 2016;Reis et al, 2009;Bouwman et al, 1997;Heald et al, 2012;Balasubramanian et al, 2015;Huang et al, 2011). In the urban atmosphere, recent studies suggest that nonagricultural activities like wastewater discharge (Zhang et al, 2017), coal burning (Li et al, 2016a), solid waste (Reche et al, 2012), on-road traffic (Suarez-Bertoa et al, 2014), and green spaces (Teng et al, 2017) also contribute to NH 3 emissions. In reactions with H 2 SO 4 and HNO 3 , NH 3 contributes to the formation of NH + 4 salts, which typically make up from 20 % to 80 % of fine particles (PM 2.5 ) in the atmosphere (Seinfeld and Pandis, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Biomass burning (BB) is an important source of N in the atmosphere (Lobert et al, 1990;Souri et al, 2017). During the harvest or hot season of eastern China, agricultural BB frequently occurs and modifies the concentration and composition of aerosols in the atmosphere Zhang and Cao, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Biomass burning (BB) is an important source of N in the atmosphere (Lobert et al, 1990;Souri et al, 2017). During the harvest/hot season of eastern China, agricultural BB frequently occurs and modifies the concentration and composition of aerosols in the atmosphere (Chen et al,70 2017; Zhang and Cao, 2015).…”
mentioning
confidence: 99%